Diachronic construction grammar - Jóhanna Barðdal,Smirnova, Elena,Sommerer, Lotte,Gildea, Spike (Philadelphia, 2015)
2. The model of the successive context types in grammaticalization3. From critical context to a new construction; 3.1 Micro- and macro-levels of change; 3.2 Between growth and decline of contextual constraints; 4. Case studies; 4.1 scheinen + zu-infinitive; 4.2 würde + infinitive; 4.3 gehören; 5. Conclusion; References; The influence of constructions in grammaticalization; 1. Introduction; 2. Revisiting the phenomenon ; 3. from a constructional perspective; 3.1 Diachronic construction grammar; 3.2 Analogy & frequency; 4. The influence of constructions on the article's emergence. 3.3.2 Colleman's contribution3.4 Grammatical relations; 3.4.1 Diachronic implications; 3.5 Usage-based approaches; 3.5.1 Diachronic implications; 3.6 Productivity; 3.6.1 Diachronic implications; 4. Afterword; References; Toward a coherent account of grammatical constructionalization; 1. Introduction; 2. A constructional account of change; 3. Grammatical constructionalization; 4. Exemplar-based change and the role of analogy; 5. BE going to revisited; 6. Conclusion; References; Constructionalization and constructional change; 1. Introduction. 3. Features relevant to the PA functional range4. Distribution of pseudo-PAs in OCz texts; 4.1 Functional range; 4.1.1 Linearization A; 4.1.2 Linearization B; 4.1.3 Linearization C; 4.2 Non-PA meanings; 5. Constructional analysis; 5.1 Representing context-motivated change; 5.2 What kind of change?; 6. Conclusions; References; On the relation between inheritance and change; 1. Introduction; 2. Corpora and method; 2.1 Corpora; 2.2 Methods; 3. The Para Infinitive family of constructions in 21st century Brazilian Portuguese; 4. The Para Infinitive family in the history of the Portuguese Language. 4.1 Main Trigger: Frequency and analogy effects on the definite NP level4.1.1 Corpus study of obligatory definiteness marking; 4.1.2 Emergence of a construction; 4.2 Additional Trigger: Influence of taxonomically related constructions; 4.2.1 Corpus study on pattern preferences in the general Old English NP; 4.2.2 Interpretation of results; 5. Conclusion; References; Manuscripts:; Electronic sources; Irregular morphology in regular syntactic patterns; 1. Introduction; 1.1 Data; 1.2 Constructional approach; 2. The morphology of Old Czech pseudo-PAs. Diachronic Construction Grammar; Editorial page; Title page; LCC data; Table of contents; In memory of Anna Siewierska; References; Diachronic Construction Grammar; 1. Introduction; 2. Pre-constructional approaches to historical linguistics; 3. The basics of construction grammar and its diachronic implications; 3.1 Form-meaning correspondence; 3.1.1 Diachronic implications; 3.1.2 Traugott's, Smirnova's, Sommerer's and Fried's contributions; 3.2 The ConstructiCon; 3.2.1 Diachronic implications; 3.2.2 Torrent's contribution; 3.3 Location on different clines; 3.3.1 Diachronic implications. The grammatical literature on Dutch generally distinguishes two
Includes bibliographical references and index
Keywords: Construction grammar; Linguistic change; Historical linguistics; LANGUAGE ARTS & DISCIPLINES; Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES; Linguistics; Syntax; Historische Sprachwissenschaft; Konstruktion; Sprachwandel